The Unlikely Alliance of Mormonism and Christian Nationalism - Park, Benjamin E. (Journal of media and religion, 2024)
American members of the Church of Jesus Christ of Latter-day Saints are typically seen as politically conservative and proponents of Christian natioanalism. However, this has not always been the case. This essay provides a historical overview of how the Mormon tradition evolved from being dissenters from America’s patriotic imagination to some of its most adamant promotors. I also highlight the paradoxes at the heart of the current cultural alliance between devout Latter-day Saints and evangelical activists.